FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI DALAM MEMILIH PLATFORM CROWDFUNDING (STUDI KASUS PADA PETANI HORTIKULTURA DI DESA SUMBEREJO, MAGELANG) - PUTU YANI PRATIWI; Ika Yanuarti; Wim Prihanto (Ultima Management : Jurnal Ilmu Manajemen, 2020)
Abstract– Agriculture crowdfunding is a new alternative financing for farmers. The purpose of this paper is to understand some added values provided by agriculture crowdfunding in Indonesia compare to traditional financing and to understand the potential demand of crowdfunding platform. This paper also explores what factors influence farmers to choose crowdfunding platform as their alternative financing. A series of in-depth interview were conducted with 3 Indonesian agriculture crowdfunding s and 30 farmers in Central Java area. These data are presented in simple form to compare the benefits of 3 agriculture crowdfunding s and to explain which benefits are interesting for the farmers. The findings in this paper are agriculture crowdfunding provides field support (agriculture expert) and crop buyers which are not provided by traditional financing. Agriculture crowdfunding asks no collateral from the farmers and use profit sharing method. Potential demand for crowdfunding is high because more than 70% of the farmers informant would like to use agriculture crowdfunding for their next source of financing. Keywords: Agriculture, Crowdfunding , Financing